The Effect Of Intellectual Capital And Firm Size To Profitability In The Banking Sector Listed On Idx - Lim, Maria Virginia; Panjaitan, Delfi (Prodi Akuntasi, Fakultas Bisnis dan Akuntansi Unika Musi Charitas, 2023)
This study aims to determine the effect of intellectual capital and firm size on profitability in the banking sector listed on the IDX. The data used is secondary data, with a population of banking sector companies listed on the IDX for the 2016-2020 period. The sampling technique used purposive sampling method and obtained 27 companies with a total sample of 135. Hypothesis testing in this study was carried out by multiple regression analysis. The results showed that Value Added Capital Employed (VACA) had no effect on profitability, Value Added Human Capital (VAHU) had no effect on profitability, Structural Capital Value Added (STVA) had no effect on profitability, and firm size had an effect on profitability.